Early IGF-1 primes visual cortex maturation and accelerates developmental switch between NKCC1 and KCC2 chloride transporters in enriched animals. (February 2017) - Baroncelli, Laura; Cenni, Maria Cristina; Melani, Riccardo; Deidda, Gabriele; Landi, Silvia; Narducci, Roberta; Cancedda, Laura; Maffei, Lamberto; Berardi, Nicoletta
Abstract: Environmental enrichment (EE) has a remarkable impact on brain development. Continuous exposure to EE from birth determines a significant acceleration of visual system maturation both at retinal and cortical levels. A pre-weaning enriched experience is sufficient to trigger the accelerated maturation of the visual system, suggesting that factors affected by EE during the first days of life might prime visual circuits towards a faster development. The search for such factors is crucial not only to gain a better understanding of the molecular hierarchy of brain development but also to identify molecular pathways amenable to be targeted to correct atypical brain developmental trajectories. Here, we showed that IGF-1 levels are increased in the visual cortex of EE rats as early as P6 and this is a crucial event for setting in motion the developmental program induced by EE. Early intracerebroventricular (i.c.v.) infusion of IGF-1 in standard rats was sufficient to mimic the action of EE on visual acuity development, whereas blocking IGF-1 signaling by i.c.v. injections of the IGF-1 receptor antagonist JB1 prevented the deployment of EE effects. Early IGF-1 decreased the ratio between the expression of NKCC1 and KCC2 cation/chloride transporters, and the reversal potential for GABAA R-driven Cl − currents (ECl ) was shifted toward more negative potentials, indicating that IGF-1 is a crucial factor in accelerating the maturation of GABAergic neurotransmission and promoting the developmental switch of GABA polarity from excitation to inhibition. In addition, early IGF-1 promoted a later occurring increase in its own expression, suggesting a priming effect of early IGF-1 in driving post-weaning cortical maturation. Highlights: Early IGF-1 is a "master organizer" of brain experience-dependent development. IGF-1 mimics the effects of early enriched experience on visual acuity. IGF-1 promotes the switch of GABAergic responses from excitation to inhibition. Living in environmental enrichment induces two distinct peaks of IGF-1 expression.